2018
DOI: 10.4236/health.2018.1011115
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Effects of High Blood Pressure on Medical Costs and Heart Disease: Is the 2017 ACC/AHA Guideline Supported by Enough Evidence?

Abstract: Background: The American College of Cardiology (ACC), American Heart Association (AHA) and other organizations announced a new hypertension guideline in November 2017. However, previous studies have pointed out that this new guideline might lack sufficient evidence to justify its use. Data and Methods: The effects of blood pressure (BP) on medical costs and on the probability of having heart disease as anamnesis are analyzed. We used a dataset containing 175,123 medical checkups and 6,312,125 receipts from 88,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the HD model, the ORs (95% CI) were 1.93 (1.83-2.02), 1.81 (1.59-2.04), 2.21 (2.06-2.36), and 2. 19 Odds ratios and 95% confidence intervals of Age (Age 50 vs. Age 70) in three models. Odds ratios and 95% confidence intervals of U_Protein and Weight_1 in three models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the HD model, the ORs (95% CI) were 1.93 (1.83-2.02), 1.81 (1.59-2.04), 2.21 (2.06-2.36), and 2. 19 Odds ratios and 95% confidence intervals of Age (Age 50 vs. Age 70) in three models. Odds ratios and 95% confidence intervals of U_Protein and Weight_1 in three models.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed the relationship between high BP or hypertension [especially high systolic BP (SBP)] and HD or CVD (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Although most of these studies indicated that hypertension is a risk factor for HD and CVD, some questioned the relationship between them (13, 18-20, 22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…They found a negative relationship between SBP and medical costs. Using the same dataset, Nawata and Kimura ( 37 ) analyzed the effects of BP on medical costs and on the probability of having a history of HD. The dataset was divided into subgroups based on whether the patients had diabetes and took antihypertension medications.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Sample-selection biases and the selection of explanatory variables were other important problems to be properly treated [49].…”
Section: Reviews Of Previous Studiesmentioning
confidence: 99%
“…More recently, Nawata and Kimura[49] [50] analyzed the total annual medical expenditures and results of BP measured using the power transformationTobit models for a dataset containing 175,123 cases obtained from 88,211 individuals. They found that the medical expenditure declined as SBP increased.…”
mentioning
confidence: 99%